Penerapan Desain Pembelajaran Tematik Integratif Berbasis Karakter Untuk Meningkatkan Hasil dan Kebermaknaan Belajar - Nur Fitri Rizkiyah; Stefanus C. Relmasira (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2018)
This study aims to improve the results and meaningfulness of student learning through the application of character-based integrative thematic learning design. This type of research is Stringer model class action research in two cycles with the look, think, and act stages. Data collection instruments use question instruments, questionnaires, observation sheets, and field notes. Data analysis uses comparative description techniques. The subjects of this study were 4th grade students of Salatiga Elementary School 03. The results showed an increase in the results and meaningfulness of student learning. The completeness of the thematic learning outcomes of students in cycle 1 for the content of Indonesian language learning is 79% and the content of the IPS lesson is 70%. In cycle 2 shows the completeness of learning outcomes for the contents of Indonesian language lessons by 88% and the content of social studies by 76%. Student meaningfulness in cycle 1 reached 76% in the meaningful category, then in cycle 2 increased by 88% in the very meaningful category. Based on the results of the study, the application of character-based integrative thematic learning design can improve the results and meaningfulness of student learning.